Jab1/COPS5 as a Novel Biomarker for Diagnosis, Prognosis, Therapy Prediction and Therapeutic Tools for Human Cancer - Liu, Guohong; Claret, Francois X.; Zhou, Fuling; Pan, Yunbao (Frontiers in Pharmacology, 2018)
C-Jun activation domain-binding protein-1 (Jab1) involves in controlling cellular proliferation, cell cycle, apoptosis, affecting a series of pathways, as well as regulating genomic instability and DNA damage response. Jab1/COPS5 dysregulation contributes to oncogenesis by deactivating several tumor suppressors and activating oncogenes. Jab1 overexpression was found in many tumor types, illuminating its important role in cancer initiation, progression, and prognosis. Jab1/COPS5 has spurred a strong research interest in developing inhibitors of oncogenes/oncoproteins for cancer therapy. In this paper, we present evidences demonstrating the importance of Jab1/COPS5 overexpression in several cancer types and recent advances in dissecting the Jab1/COPS5 upstream and downstream signaling pathways. By conducting ingenuity pathway analysis (IPA) based on the Ingenuity Knowledge Base, and querying the web-based oncomine microarray database, we investigated signaling network that interacts with Jab1/COPS5. The data confirmed the important role of Jab1/COPS5 in tumorigenesis, demonstrating the potential of Jab1/COPS5 to be used as a biomarker for cancer patients, and further support that Jab1/COPS5 may serve as a potential therapeutic target in different cancers.